Aging-resistant rubber sealing ring material and preparation method thereof

CN122898069APending Publication Date: 2026-10-13ANHUI TONGFENG RUBBER & PLASTIC IND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611187388.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0002]橡胶密封件是液压、燃气、管道、工程机械高温工况设备中核心密封基础部件,三元乙丙、丁腈、氟橡胶类密封圈凭借基础耐候、耐介质优势得到大范围应用,但长期在120℃及以上连续高温热氧环境服役时,材料易出现分子链氧化断裂、交联网络持续降解问题,直接表现为拉伸力学衰减、压缩永久变形增大、密封回弹性能快速劣化,大幅缩短密封件更换周期,提升设备运维成本周期,提升设备运维成本

Benefits of technology

1、本发明采用八氨基苯基笼型倍半硅氧烷接枝环氧受阻酚构建单分子分散型防老剂,由于笼型硅氧烷刚性笼状骨架通过共价键与受阻酚抗氧化基团牢牢结合,一方面大幅提升防老组分整体分子量,消除小分子受阻酚易迁移析出的固有缺陷,从而能够在橡胶基体内部长期均匀留存抗氧化活性位点,进而持续捕获热氧老化产生的烷基、过氧自由基,阻断橡胶分子链氧化链式反应,解决传统小分子防老剂短期有效、长期失效的老化防护短板;另一方面笼型硅氧烷无机骨架具备优异高温热稳定性,可在材料内部构建微观隔热屏障,弱化高温热量向橡胶基体内部传导,进一步降低橡胶分子链热裂解速率,同步缓解高温环境下密封材料力学性能快速衰减的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of rubber, in particular to an anti-aging rubber sealing ring material and a preparation method thereof, which is prepared from the following raw material components: base rubber, modified cage type silsesquioxane antioxidant, interfacial hybrid nanocellulose reinforcing agent, a vulcanization system and a processing aid; the application is prepared by limiting the proportion of the base rubber, the modified cage type silsesquioxane antioxidant, the interfacial hybrid nanocellulose reinforcing agent, the compounded vulcanization system and the processing aid, matching the preparation process of the modified auxiliary agent, the segmented nitrogen mixing, the nitrogen temperature control and the secondary vulcanization full-set integrated technical scheme, relying on the multiple synergistic effects of the microcosmic chemical bonding and the macroscopic network mutual support of each functional component, solving the three core technical defects of the traditional rubber sealing ring material, namely the antioxidant migration, the filler interface defect and the uneven crosslinking network, and simultaneously realizing the synchronous improvement of the high-temperature long-acting anti-aging, the high tensile mechanical strength and the low high-temperature compression permanent deformation performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of rubber technology, specifically to an aging-resistant rubber sealing ring material and its preparation method. Background Technology

[0002] Rubber seals are core sealing components in high-temperature equipment such as hydraulic, gas, pipeline, and construction machinery. EPDM, nitrile, and fluororubber seals are widely used due to their basic weather resistance and media resistance. However, when used in continuous high-temperature and thermo-oxidative environments at 120°C and above for extended periods, the materials are prone to molecular chain oxidation and breakage, as well as continuous degradation of the cross-linked network. This directly manifests as tensile mechanical attenuation, increased permanent compression deformation, and rapid deterioration of sealing resilience, significantly shortening the seal replacement cycle and increasing equipment maintenance costs.

[0003] Current industry-standard modification methods are mainly divided into two categories: reinforcement modification and anti-aging modification. Both types of modification schemes have significant technical shortcomings. The first type of conventional reinforcement scheme directly uses unmodified nanocellulose powder to fill the rubber matrix. The surface of nanocellulose is rich in a large number of hydrophilic hydroxyl groups, which have extremely poor interfacial compatibility with the non-polar rubber matrix. During the mixing and processing stage, the powder is prone to agglomeration, forming internal defects and pores. During the stress process, the stress cannot be effectively transferred between the filler and the rubber phase. This not only fails to achieve efficient reinforcement but also simultaneously exacerbates the intrusion of thermo-oxidative media into the material along the interfacial voids, accelerating rubber aging and failure. Some schemes use a single silane coupling agent to simply modify cellulose, which can only slightly reduce the content of surface hydrophilic groups and cannot build an interfacial layer that is stably bonded to the rubber molecular chain. The interfacial slip defect still cannot be eliminated. The second type of traditional anti-aging modification method often involves directly adding small-molecule hindered phenolic antioxidants. These small-molecule antioxidants have low molecular weight and weak binding force with the rubber matrix. Under long-term high-temperature conditions, they will continue to migrate and precipitate to the material surface. They have a certain anti-aging effect in the short term, but after long-term use, a large amount of antioxidant components are lost, and the ability to capture free radicals is rapidly lost. Some other methods simply physically blend inorganic siloxane powder with small-molecule antioxidants. The two are only physically mixed without chemical bonding. At high temperatures, the two phases separate, and the siloxane cannot fix the antioxidant molecules. This also fails to solve the core problem of antioxidant migration and loss.

[0004] Based on this, the present invention provides an aging-resistant rubber sealing ring material to solve the above problems. Summary of the Invention

[0005] To achieve the above objectives, the present invention provides the following technical solution: An aging-resistant rubber sealing ring material is made from the following raw material components in parts by weight: 80-100 parts of base rubber, 3-8 parts of modified cage-type silsesquioxane antioxidant, 5-15 parts of interface hybrid nanocellulose reinforcing agent, 2-5 parts of vulcanization system, and 1-3 parts of processing aid. The modified cage-type silsesquioxane antioxidant is a monomolecular dispersible antioxidant prepared by grafting octaaminophenyl cage-type silsesquioxane with an epoxy-containing hindered phenolic compound.

[0006] As a further technical solution, the base rubber is at least one of EPDM rubber, nitrile rubber, and fluororubber.

[0007] As a further technical solution, the preparation method of the modified cage-type silsesquioxane antioxidant includes the following steps: An OAPS dispersion with a mass fraction of 5%-8% was prepared by uniformly dispersing octaaminophenyl cage-type silsesquioxane in anhydrous toluene. Under a high-purity nitrogen protective atmosphere in an ice bath at 0-5℃, an anhydrous toluene solution of a hindered phenolic compound containing an epoxy group was slowly added dropwise to the dispersion. The molar ratio of octaaminophenyl cage-type silsesquioxane to the hindered phenolic compound containing an epoxy group was 1:1.5-2.5. After the addition was completed, the temperature was raised to 75-85℃ at a uniform rate and refluxed for 6-10 hours.

[0008] After the reaction is completed, 60%-70% of the anhydrous toluene solvent is removed by vacuum distillation of the reaction solution. Then, petroleum ether with a volume of 2-3 times that of the remaining reaction solution is added and the mixture is allowed to stand for 2-4 hours to precipitate. The solid precipitate is collected by vacuum filtration and the filter cake is washed three times with anhydrous toluene. The washed filter cake is then dried in a vacuum drying oven at 60-70℃ for 12-16 hours to obtain the modified cage-type silsesquioxane antioxidant.

[0009] As a further technical solution, the hindered phenolic compound containing an epoxy group is glycidyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0010] As a further technical solution, the preparation method of the interface hybrid nanocellulose reinforcing agent includes the following steps: S1 Hydrophobic Modification: A 2%-5% solid content aqueous dispersion of nanocellulose crystals is ultrasonically dispersed for 30-60 minutes at room temperature and 200-300W power. Silane coupling agent KH-570 is added at 8%-12% of the dry weight of the nanocellulose crystals. The pH of the system is precisely adjusted to 4-5 using glacial acetic acid. Modification is carried out for 2-3 hours under constant temperature water bath at 60℃ and uniform stirring. After modification, the solid product is separated by centrifugation at 8000-10000 r / min. The solid product is repeatedly washed with deionized water until the filtrate is neutral to obtain hydrophobically modified nanocellulose.

[0011] S2 Interface Grafting: The hydrophobic modified nanocellulose is uniformly dispersed in xylene solvent at a solid-liquid mass ratio of 1:20-30. Liquid carboxylated nitrile rubber with a dry weight mass ratio of 2-3:1 to the hydrophobic modified nanocellulose is added. The mixture is stirred at room temperature and 300-500 r / min for 30 min to form a homogeneous suspension. Dibutyltin dilaurate catalyst, accounting for 0.5%-1% of the mass of the liquid carboxylated nitrile rubber, is added to the suspension. The mixture is then refluxed at 110-120℃ under normal pressure for 1-2 h.

[0012] S3 Post-processing: After the reaction is completed, the reaction system is immediately cooled to room temperature in an ice-water bath. Anhydrous ethanol with a volume of 2-3 times the total volume of the reaction system is added to precipitate the solid product. The solid precipitate is completely collected by vacuum filtration. The filter cake is placed in a vacuum drying oven at 60℃ and a vacuum degree ≥-0.08MPa and dried to constant weight to obtain the interfacial hybrid nanocellulose reinforcing agent.

[0013] As a further technical solution, the vulcanization system is uniformly compounded from sulfur, accelerator DM, and accelerator TMTD in a mass ratio of 1:0.8-1.2:0.5-0.8, and the particle size of the compounded vulcanization system powder is 200-300 mesh.

[0014] As a further technical solution, the processing aid is at least one of stearic acid, polyethylene wax, and paraffin wax.

[0015] The preparation method of the aging-resistant rubber sealing ring material includes the following steps: S1 Plasticizing: Place the base rubber on a two-roll mill, set the roll gap to 1-2mm, and perform thin-pass plasticizing 8-12 times at room temperature. Monitor the Mooney viscosity of the rubber compound in real time until the Mooney viscosity of the rubber compound is stably maintained in the range of 60±5 and the value of the test is stable for three consecutive times without fluctuation. The plasticizing of the base rubber is then complete.

[0016] S2 Mixing: The plasticized rubber compound is put into a closed internal mixer. First, the interfacial hybrid nanocellulose reinforcing agent is added and mixed for 2-3 minutes. Then, the modified cage-type silsesquioxane antioxidant and processing aid are added in sequence. High-purity nitrogen gas with a purity of ≥99.5% is introduced throughout the process for protection. The segmented speed-regulating mixing mode is adopted, and the total rotor speed range is controlled at 40-60 rpm. The total mixing time is 15-20 minutes. The discharge temperature is controlled not to exceed 100℃ throughout the process to obtain a uniformly dispersed compound.

[0017] S3 One-Step Vulcanization Molding: The prepared compound is transferred to a two-roll mill, and the proportioned vulcanization system is added. The mixture is repeatedly rolled 5-8 times to ensure that the additives are evenly dispersed throughout the compound. After being cut into sheets, the mixture is placed in a flat vulcanizing machine. The preformed sealing ring is then molded and vulcanized for 20-25 minutes at a vulcanization temperature of 150-170℃ and a vulcanization pressure of 10-15MPa to obtain the sealing ring preform.

[0018] S4 Nitrogen Atmosphere Secondary Vulcanization: The pre-formed sealing ring after vulcanization is placed stably inside a nitrogen-filled oven, maintaining a nitrogen concentration of ≥99.5% in the oven, and heat-treated at a constant temperature of 160-180℃ for 2-4 hours. After heat treatment, the material is discharged naturally to room temperature to obtain an aging-resistant rubber sealing ring material.

[0019] As a further technical solution, the segmented mixing in step S2 is specifically divided into two-stage speed-regulating mixing stages: the first stage has a rotor speed of 40 rpm and constant temperature mixing for 8-10 min; the second stage increases the rotor speed to 60 rpm and constant temperature mixing for 7-10 min.

[0020] As a further technical solution, in the secondary vulcanization process described in step S4, the heating rate of the oven is strictly controlled to be 3-5℃ / min.

[0021] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention employs an octaaminophenyl cage-like silsesquioxane grafted with epoxy hindered phenol to construct a monomolecular dispersed antioxidant. Because the rigid cage-like skeleton of the cage-like siloxane is firmly bonded to the antioxidant groups of the hindered phenol via covalent bonds, it significantly increases the overall molecular weight of the antioxidant component, eliminating the inherent defect of easy migration and precipitation of small-molecule hindered phenol. This allows for the long-term uniform retention of antioxidant active sites within the rubber matrix, continuously capturing alkyl and peroxy free radicals generated by thermo-oxidative aging, blocking the oxidation chain reaction of the rubber molecular chain, and solving the shortcoming of traditional small-molecule antioxidants that are effective in the short term but fail in the long term. Furthermore, the cage-like siloxane inorganic skeleton possesses excellent high-temperature thermal stability, which can construct a microscopic thermal barrier within the material, weakening the conduction of high-temperature heat to the interior of the rubber matrix, further reducing the thermal decomposition rate of the rubber molecular chain, and simultaneously alleviating the problem of rapid degradation of the mechanical properties of sealing materials under high-temperature environments.

[0022] 2. This invention designs a hybrid nanocellulose reinforcing agent based on hydrophobically modified and interfacially grafted liquid carboxylated butadiene-acrylonitrile rubber. Because the hydroxyl groups on the cellulose surface are hydrophobically modified with a silane coupling agent, and then rubber segments are grafted via a carboxyl-epoxy esterification reaction, a chemically bonded interface is formed between the filler and the matrix. There are no hydrophilic-hydrophobic interfacial voids, thus achieving uniform dispersion of individual nanocellulose strands without agglomeration. This efficiently transfers external stress, improves the tensile strength and dimensional stability of the rubber, and solves the defects of poor compatibility and low reinforcing efficiency of unmodified nanocellulose. It is equipped with segmented speed-regulating nitrogen protection. The internal mixing process first disperses the filler at a low speed, then mixes the functional additives uniformly at a high speed. The entire process is oxygen-free, avoiding premature oxidation of the rubber during the mixing stage. This ensures uniform dispersion of the two core functional additives and prevents performance inconsistencies caused by local additive enrichment or deficiency. The nitrogen atmosphere temperature-controlled secondary vulcanization process, due to the inert atmosphere preventing air oxidation, slowly raises the temperature to gradually improve the rubber crosslinking network, eliminating uncrosslinked chain segments and small molecule byproducts remaining from the first vulcanization, thereby improving the overall crosslinking density uniformity. This, in turn, reduces molecular chain slippage and rebound loss under high-temperature compression, and improves sealing and rebound performance. The continuous organic-inorganic hybrid network formed by the interface-hybridized nanocellulose can physically bind and modify the cage-like silsesquioxane antioxidant, further inhibiting the trace migration of antioxidant molecules; nitrogen-sealed mixing can completely preserve the active phenolic hydroxyl groups of the antioxidant, avoiding high-temperature oxidation deactivation during mixing; after secondary vulcanization to improve the cross-linking network, the density of the rubber matrix is ​​improved, and the channels for oxygen and thermo-oxygen media to penetrate into the material are greatly reduced. Together with the free radical capturing function of the modified siloxane antioxidant, it forms a dual anti-aging protection system inside and outside. A single component cannot achieve this composite protection effect.

[0023] 3. This invention utilizes a complete integrated technical solution that combines a base rubber, a modified cage-type silsesquioxane antioxidant, an interfacial hybrid nanocellulose reinforcing agent, a compound vulcanization system, and processing aids in a defined ratio. This solution, along with a matching modified additive preparation process, segmented nitrogen mixing, and nitrogen-controlled temperature secondary vulcanization, leverages the synergistic effects of the microscopic chemical bonds and macroscopic network support of the functional components. On one hand, it addresses the three core technical defects of traditional rubber sealing ring materials: antioxidant migration, filler interface defects, and uneven cross-linking networks. On the other hand, it simultaneously improves three key performance characteristics: long-term high-temperature aging resistance, high tensile mechanical strength, and low-temperature compression set. Under long-term high-temperature sealing conditions, the material exhibits significantly improved mechanical property retention after aging, and a significantly slower rate of seal rebound decay. This effectively extends the service life of rubber sealing rings, reduces the frequency of equipment seal replacement, and lowers industrial equipment maintenance costs. Furthermore, the entire preparation process is controllable, the raw materials are stably dispersed, and it is suitable for industrial mass production, demonstrating significant industrial application value. Detailed Implementation

[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0025] This invention provides an aging-resistant rubber sealing ring material, made from the following raw material components in parts by weight: 80-100 parts of base rubber, 3-8 parts of modified cage-type silsesquioxane antioxidant, 5-15 parts of interfacial hybrid nanocellulose reinforcing agent, 2-5 parts of vulcanization system, and 1-3 parts of processing aid. The modified cage-type silsesquioxane antioxidant is a monomolecular dispersible antioxidant obtained by grafting octaaminophenyl cage-type silsesquioxane with an epoxy-containing hindered phenolic compound.

[0026] In this invention, the matrix rubber is preferably at least one of EPDM rubber, nitrile rubber, and fluororubber, and more preferably EPDM rubber.

[0027] In this invention, the preferred method for preparing the modified cage-type silsesquioxane antioxidant includes the following steps: uniformly dispersing octaaminophenyl cage-type silsesquioxane in anhydrous toluene to prepare an OAPS dispersion with a mass fraction of 5%-8%; slowly adding an anhydrous toluene solution of a hindered phenolic compound containing epoxy groups to the dispersion under an ice bath at 0-5°C and a high-purity nitrogen protective atmosphere; wherein the molar ratio of octaaminophenyl cage-type silsesquioxane to the hindered phenolic compound containing epoxy groups is 1:1.5-2.5; after the addition is completed, uniformly heating to 75-85°C and refluxing at a constant temperature for 6-10 hours. After the reaction is completed, 60%-70% of the anhydrous toluene solvent is removed by vacuum distillation of the reaction solution. Then, petroleum ether with a volume of 2-3 times that of the remaining reaction solution is added and the mixture is allowed to stand for 2-4 hours to precipitate. The solid precipitate is collected by vacuum filtration and the filter cake is washed three times with anhydrous toluene. The washed filter cake is then dried in a vacuum drying oven at 60-70℃ for 12-16 hours to obtain the modified cage-type silsesquioxane antioxidant.

[0028] In this invention, the hindered phenolic compound containing epoxy groups is preferably glycidyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate. The molar ratio of the octaaminophenyl cage-type silsesquioxane to the hindered phenolic compound containing epoxy groups is more preferably 1:2; the isothermal reflux reaction temperature is more preferably 80°C, and the reaction time is more preferably 8 hours; the vacuum drying temperature is more preferably 65°C, and the drying time is more preferably 14 hours.

[0029] In this invention, the preferred method for preparing the interface hybrid nanocellulose reinforcing agent includes the following steps: S1 Hydrophobic modification: A nanocellulose crystal aqueous dispersion with a solid content of 2%-5% is ultrasonically dispersed for 30-60 min at room temperature and power of 200-300W; Silane coupling agent KH-570 is added at 8%-12% of the dry weight of nanocellulose crystals, and the pH value of the system is precisely adjusted to 4-5 using glacial acetic acid. Modification is carried out for 2-3 h under constant temperature water bath at 60℃ and uniform stirring; After modification, the solid product is separated by centrifugation at 8000-10000 r / min, and the solid product is repeatedly washed with deionized water until the filtrate is neutral to obtain hydrophobic modified nanocellulose. S2 Interface Grafting: The hydrophobic modified nanocellulose is uniformly dispersed in xylene solvent at a solid-liquid mass ratio of 1:20-30. Liquid carboxylated nitrile rubber with a dry weight mass ratio of 2-3:1 to the hydrophobic modified nanocellulose is added, and the mixture is stirred at room temperature and 300-500 r / min for 30 min to form a homogeneous suspension. Dibutyltin dilaurate catalyst (0.5%-1% by mass of liquid carboxylated nitrile rubber) is added to the suspension, and the mixture is refluxed at 110-120℃ under normal pressure for 1-2 h. S3 Post-treatment: After the reaction, the reaction system is immediately cooled rapidly to room temperature in an ice-water bath. Anhydrous ethanol (2-3 times the total volume of the reaction system) is added to precipitate the solid product. The solid precipitate is completely collected by vacuum filtration, and the filter cake is dried to constant weight in a vacuum drying oven at 60℃ and a vacuum degree ≥-0.08 MPa to obtain the interface hybrid nanocellulose reinforcing agent.

[0030] In this invention, the amount of silane coupling agent KH-570 added is more preferably 10% of the dry weight of nanocellulose crystals; the modification reaction time is more preferably 2.5 h; the mass ratio of the liquid carboxylated acrylonitrile rubber to the dry weight of hydrophobic modified nanocellulose is more preferably 2.5:1; the isothermal reflux reaction temperature is more preferably 115 °C, and the reaction time is more preferably 1.5 h.

[0031] In this invention, the vulcanization system is preferably composed of sulfur, accelerator DM, and accelerator TMTD in a mass ratio of 1:0.8-1.2:0.5-0.8, and the particle size of the powder of the vulcanization system after compounding is preferably 200-300 mesh; the mass ratio of sulfur, accelerator DM, and accelerator TMTD is more preferably 1:1:0.65, and the particle size is more preferably 250 mesh.

[0032] In this invention, the processing aid is preferably at least one of stearic acid, polyethylene wax, and paraffin wax, and more preferably a mixture of stearic acid and polyethylene wax in a mass ratio of 1:1.

[0033] The present invention also provides a method for preparing the aging-resistant rubber sealing ring material, comprising the following steps: S1 Plasticizing: Place the base rubber on a two-roll mill, set the roll gap to 1-2mm, and perform thin-pass plasticizing 8-12 times at room temperature. Monitor the Mooney viscosity of the rubber compound in real time until the Mooney viscosity of the rubber compound is stably maintained in the range of 60±5 and the value of the test is stable for three consecutive times without fluctuation. The plasticizing of the base rubber is then complete.

[0034] S2 Mixing: The plasticized rubber compound is put into a closed internal mixer. First, the interfacial hybrid nanocellulose reinforcing agent is added and mixed for 2-3 minutes. Then, the modified cage-type silsesquioxane antioxidant and processing aid are added in sequence. High-purity nitrogen gas with a purity of ≥99.5% is introduced throughout the process for protection. The segmented speed-regulating mixing mode is adopted, and the total rotor speed range is controlled at 40-60 rpm. The total mixing time is 15-20 minutes. The discharge temperature is controlled not to exceed 100℃ throughout the process to obtain a uniformly dispersed compound.

[0035] S3 One-Step Vulcanization Molding: The prepared compound is transferred to a two-roll mill, and the proportioned vulcanization system is added. The mixture is repeatedly rolled 5-8 times to ensure that the additives are evenly dispersed throughout the compound. After being cut into sheets, the mixture is placed in a flat vulcanizing machine. The preformed sealing ring is then molded and vulcanized for 20-25 minutes at a vulcanization temperature of 150-170℃ and a vulcanization pressure of 10-15MPa to obtain the sealing ring preform.

[0036] S4 Nitrogen Atmosphere Secondary Vulcanization: The pre-formed sealing ring after vulcanization is placed stably inside a nitrogen-filled oven, maintaining a nitrogen concentration of ≥99.5% in the oven, and heat-treated at a constant temperature of 160-180℃ for 2-4 hours. After heat treatment, the material is discharged naturally to room temperature to obtain an aging-resistant rubber sealing ring material.

[0037] In this invention, the roller gap in step S1 is more preferably 1.5 mm, and the number of thin-pass plasticizing cycles is more preferably 10. Step S2, the segmented mixing, is specifically divided into two-stage speed-adjustable mixing stages: the first stage has a rotor speed of 40 rpm and isothermal mixing for 8-10 min; the second stage increases the rotor speed to 60 rpm and isothermal mixing for 7-10 min; the mixing time in the first stage is more preferably 9 min, and the mixing time in the second stage is more preferably 8.5 min. Step S3, the vulcanization temperature is more preferably 160℃, the vulcanization pressure is more preferably 12.5 MPa, and the molding vulcanization time is more preferably 22.5 min. Step S4, the secondary vulcanization is more preferably at a constant temperature of 170℃, and the heat treatment time is more preferably 3 h; during the secondary vulcanization process, the oven heating rate is strictly controlled at 3-5℃ / min, more preferably 4℃ / min.

[0038] The aging-resistant rubber sealing ring material provided by this invention uses a modified cage-type silsesquioxane antioxidant and an interface hybrid nanocellulose reinforcing agent as core functional components. Combined with a segmented mixing and nitrogen secondary vulcanization process, the components achieve a synergistic effect, which can significantly improve the thermo-oxidative aging resistance and mechanical reinforcement of the rubber material, effectively reduce compression set under high-temperature conditions, and extend the service life of the sealing ring. At the same time, the preparation process has good dispersibility, the additives are not easy to migrate and precipitate, and the finished product has high dimensional stability. It is suitable for the batch production of various irregular-shaped sealing rings, which can improve the production yield and shorten the processing cycle.

[0039] Compared with existing technologies, the aging-resistant rubber sealing ring material provided by this invention constructs a monomolecular dispersion anti-aging system by grafting hindered phenol onto cage-type silsesquioxane, which solves the problems of easy migration and precipitation and poor long-term effectiveness of traditional anti-aging agents; through interface hybridization modification of nanocellulose, a strong interfacial bond with the rubber matrix is ​​achieved, which improves the reinforcement efficiency and the material's resistance to compression deformation; combined with nitrogen secondary vulcanization to optimize the crosslinked network structure, the long-term stability of the material is further improved, and the overall aging resistance, mechanical properties and sealing performance are simultaneously improved.

[0040] To further illustrate the present invention, the following embodiments will be described in detail.

[0041] Example 1: Preparation of modified cage-type silsesquioxane antioxidant: Octaaminophenyl cage-type silsesquioxane was uniformly dispersed in anhydrous toluene to prepare a 5% (w / w) OAPS dispersion. Under a 0°C ice bath and a high-purity nitrogen protective atmosphere, an anhydrous toluene solution of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was slowly added dropwise to the dispersion. The molar ratio of octaaminophenyl cage-type silsesquioxane to 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was 1:1.5. After the addition was complete, the temperature was uniformly raised to 75°C and refluxed for 6 hours. After the reaction was completed, 60% of the anhydrous toluene solvent was removed by vacuum distillation of the reaction solution. Then, petroleum ether with a volume twice that of the remaining reaction solution was added and allowed to stand for 2 hours to precipitate. The solid precipitate was collected by vacuum filtration and the filter cake was washed three times with anhydrous toluene. The washed filter cake was then dried in a vacuum drying oven at 60°C for 12 hours to obtain the modified cage-type silsesquioxane antioxidant.

[0042] Preparation of interfacial hybrid nanocellulose reinforcing agents: S1 Hydrophobic Modification: The aqueous dispersion of nanocellulose crystals was diluted to a solid content of 2% and ultrasonically dispersed for 30 min at room temperature and 200W power. Silane coupling agent KH-570 was added at 8% of the dry weight of the nanocellulose crystals. The pH of the system was precisely adjusted to 4 using glacial acetic acid. Modification was carried out for 2 h under constant temperature water bath at 60℃ and uniform stirring. After modification, the solid product was separated by centrifugation at 8000 r / min and repeatedly washed with deionized water until the filtrate was neutral, thus obtaining hydrophobically modified nanocellulose.

[0043] S2 Interface Grafting: The hydrophobic modified nanocellulose was uniformly dispersed in xylene solvent at a solid-liquid mass ratio of 1:20. Liquid carboxylated acrylonitrile rubber with a dry weight mass ratio of 2:1 to the hydrophobic modified nanocellulose was added. The mixture was stirred at room temperature and 300 r / min for 30 min to form a homogeneous suspension. Dibutyltin dilaurate catalyst, accounting for 0.5% of the mass of the liquid carboxylated acrylonitrile rubber, was added to the suspension. The mixture was then refluxed at 110℃ under normal pressure for 1 h.

[0044] S3 Post-processing: After the reaction is completed, the reaction system is immediately cooled to room temperature in an ice-water bath. Anhydrous ethanol with a volume twice the total volume of the reaction system is added to precipitate the solid product. The solid precipitate is completely collected by vacuum filtration. The filter cake is placed in a vacuum drying oven at 60℃ and a vacuum degree ≥-0.08MPa and dried to constant weight to obtain the interfacial hybrid nanocellulose reinforcing agent.

[0045] Preparation of aging-resistant rubber sealing ring materials: S1 Plasticizing: Place 80 parts by weight of EPDM rubber on a two-roll mill, set the roll gap to 1 mm, and perform thin-pass plasticizing 8 times at room temperature. Monitor the Mooney viscosity of the rubber compound in real time until the Mooney viscosity of the rubber compound is stably maintained in the range of 60±5 and the value of the test is stable for three consecutive times without fluctuation. The plasticizing of the base rubber is then completed.

[0046] S2 Mixing: The plasticized rubber compound is fed into a closed internal mixer. First, 5 parts by weight of interfacial hybrid nanocellulose reinforcing agent are added and mixed for 2 minutes. Then, 3 parts by weight of modified cage-type silsesquioxane antioxidant and 1 part by weight of processing aid are added sequentially. High-purity nitrogen gas with a purity ≥99.5% is purged throughout the process for protection. A segmented speed-controlled mixing mode is adopted. In the first stage, the rotor speed is 40 rpm and the mixture is mixed at a constant temperature for 8 minutes. In the second stage, the rotor speed is increased to 60 rpm and the mixture is mixed at a constant temperature for 7 minutes. The total mixing time is 15 minutes. The discharge temperature is controlled not to exceed 100℃ throughout the process to obtain a uniformly dispersed compound. The vulcanization system is uniformly compounded from sulfur, accelerator DM, and accelerator TMTD in a mass ratio of 1:0.8:0.5. The particle size of the compounded vulcanization system powder is 200 mesh.

[0047] S3 Single-stage vulcanization molding: The prepared compound is transferred to a two-roll mill, and 2 parts by weight of the vulcanization system are added. The mixture is repeatedly rolled 5 times to ensure uniform dispersion of the additives throughout the compound. After sheeting, the mixture is placed in a flat vulcanizing machine. It is then molded and vulcanized for 20 minutes at a vulcanization temperature of 150℃ and a vulcanization pressure of 10MPa to obtain the sealing ring preform. S4 Secondary vulcanization in nitrogen atmosphere: The vulcanized sealing ring preform is placed stably inside a nitrogen-filled oven, maintaining a nitrogen concentration ≥99.5% in the oven. The oven heating rate is controlled at 3℃ / min, and the mixture is heat-treated at a constant temperature of 160℃ for 2 hours. After heat treatment, the mixture is naturally cooled to room temperature and discharged to obtain the aging-resistant rubber sealing ring material.

[0048] Example 2: Preparation of modified cage-type silsesquioxane antioxidant: Octaaminophenyl cage-type silsesquioxane was uniformly dispersed in anhydrous toluene to prepare an OAPS dispersion with a mass fraction of 8%. Under a 5°C ice bath and a high-purity nitrogen protective atmosphere, an anhydrous toluene solution of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was slowly added dropwise to the dispersion. The molar ratio of octaaminophenyl cage-type silsesquioxane to 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was 1:2.5. After the addition was complete, the temperature was uniformly raised to 85°C and refluxed for 10 hours. After the reaction was completed, 70% of the anhydrous toluene solvent was removed by vacuum distillation of the reaction solution. Then, petroleum ether with a volume of 3 times that of the remaining reaction solution was added and allowed to stand for 4 hours to precipitate. The solid precipitate was collected by vacuum filtration and the filter cake was washed repeatedly with anhydrous toluene 3 times. The washed filter cake was placed in a vacuum drying oven at 70°C and dried for 16 hours to obtain the modified cage-type silsesquioxane antioxidant.

[0049] Preparation of interfacial hybrid nanocellulose reinforcing agents: S1 Hydrophobic Modification: The aqueous dispersion of nanocellulose crystals was diluted to a solid content of 5% and ultrasonically dispersed for 60 min at room temperature and 300 W power. Silane coupling agent KH-570 was added at 12% of the dry weight of the nanocellulose crystals. The pH of the system was precisely adjusted to 5 using glacial acetic acid. Modification was carried out for 3 h under constant temperature water bath at 60℃ and uniform stirring. After modification, the solid product was separated by centrifugation at 10000 r / min and repeatedly washed with deionized water until the filtrate was neutral, thus obtaining hydrophobic modified nanocellulose.

[0050] S2 interface grafting: The hydrophobic modified nanocellulose was uniformly dispersed in xylene solvent at a solid-liquid mass ratio of 1:30. Liquid carboxylated nitrile rubber with a dry weight mass ratio of 3:1 to the hydrophobic modified nanocellulose was added. The mixture was stirred at room temperature and 500 r / min for 30 min to form a homogeneous suspension. Dibutyltin dilaurate catalyst, accounting for 1% of the mass of the liquid carboxylated nitrile rubber, was added to the suspension. The mixture was then refluxed at 120℃ under normal pressure for 2 h.

[0051] S3 Post-processing: After the reaction is completed, the reaction system is immediately cooled to room temperature in an ice-water bath. Anhydrous ethanol with a volume of 3 times the total volume of the reaction system is added to precipitate the solid product. The solid precipitate is completely collected by vacuum filtration. The filter cake is placed in a vacuum drying oven at 60℃ and a vacuum degree ≥-0.08MPa and dried to constant weight to obtain the interfacial hybrid nanocellulose reinforcing agent.

[0052] Preparation of aging-resistant rubber sealing ring materials: S1 Plasticizing: Place 100 parts by weight of EPDM rubber on a two-roll mill, set the roll gap to 2mm, and perform thin-pass plasticizing 12 times at room temperature. Monitor the Mooney viscosity of the rubber compound in real time until the Mooney viscosity of the rubber compound is stably maintained in the range of 60±5 and the value of the test is stable for three consecutive times without fluctuation. The plasticizing of the base rubber is then completed.

[0053] S2 Mixing: The plasticized rubber compound is fed into a closed internal mixer. First, 15 parts by weight of interfacial hybrid nanocellulose reinforcing agent are added and mixed for 3 minutes. Then, 8 parts by weight of modified cage-type silsesquioxane antioxidant and 3 parts by weight of processing aid are added sequentially. High-purity nitrogen gas with a purity ≥99.5% is purged throughout the process for protection. A segmented speed-controlled mixing mode is adopted. In the first stage, the rotor speed is 40 rpm and the mixture is mixed at a constant temperature for 10 minutes. In the second stage, the rotor speed is increased to 60 rpm and the mixture is mixed at a constant temperature for 10 minutes. The total mixing time is 20 minutes. The discharge temperature is controlled not to exceed 100℃ throughout the process to obtain a uniformly dispersed compound. The vulcanization system is uniformly compounded from sulfur, accelerator DM, and accelerator TMTD in a mass ratio of 1:1.2:0.8. The particle size of the compounded vulcanization system powder is 300 mesh.

[0054] S3 Single-stage vulcanization molding: The prepared rubber compound is transferred to a two-roll mill, and 5 parts by weight of the vulcanization system are added. The mixture is repeatedly rolled 8 times to ensure uniform dispersion of the additives throughout the compound. After sheeting, the compound is placed in a flat vulcanizing machine. It is then molded and vulcanized for 25 minutes at a vulcanization temperature of 170℃ and a vulcanization pressure of 15MPa to obtain the sealing ring preform. S4 Secondary vulcanization in nitrogen atmosphere: The vulcanized sealing ring preform is placed stably inside a nitrogen-filled oven, maintaining a nitrogen concentration ≥99.5% in the oven. The oven heating rate is controlled at 5℃ / min, and the mixture is heat-treated at a constant temperature of 180℃ for 4 hours. After heat treatment, the mixture is naturally cooled to room temperature and discharged to obtain the aging-resistant rubber sealing ring material.

[0055] Example 3: Preparation of modified cage-type silsesquioxane antioxidant: Octaaminophenyl cage-type silsesquioxane was uniformly dispersed in anhydrous toluene to prepare an OAPS dispersion with a mass fraction of 6.5%. Under a 2.5°C ice bath and a high-purity nitrogen protective atmosphere, an anhydrous toluene solution of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was slowly added dropwise to the dispersion. The molar ratio of octaaminophenyl cage-type silsesquioxane to 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate was 1:2. After the addition was complete, the temperature was uniformly raised to 80°C and refluxed for 8 hours. After the reaction was completed, 65% of the anhydrous toluene solvent was removed by vacuum distillation of the reaction solution. Then, petroleum ether with a volume of 2.5 times that of the remaining reaction solution was added and allowed to stand for 3 hours to precipitate. The solid precipitate was collected by vacuum filtration and the filter cake was washed three times with anhydrous toluene. The washed filter cake was then dried in a vacuum drying oven at 65°C for 14 hours to obtain the modified cage-type silsesquioxane antioxidant.

[0056] Preparation of interfacial hybrid nanocellulose reinforcing agents: S1 Hydrophobic Modification: The aqueous dispersion of nanocellulose crystals was diluted to a solid content of 3.5% and ultrasonically dispersed for 45 min at room temperature and 250 W power. Silane coupling agent KH-570 was added at 10% of the dry weight of the nanocellulose crystals. The pH of the system was precisely adjusted to 4.5 using glacial acetic acid. Modification was carried out for 2.5 h under constant temperature water bath at 60℃ and uniform stirring. After modification, the solid product was separated by centrifugation at 9000 r / min and repeatedly washed with deionized water until the filtrate was neutral, thus obtaining hydrophobically modified nanocellulose.

[0057] S2 Interface Grafting: The hydrophobic modified nanocellulose was uniformly dispersed in xylene solvent at a solid-liquid mass ratio of 1:25. Liquid carboxylated nitrile rubber with a dry weight mass ratio of 2.5:1 to the hydrophobic modified nanocellulose was added, and the mixture was stirred at room temperature and 400 r / min for 30 min to form a homogeneous suspension. Dibutyltin dilaurate catalyst, accounting for 0.75% of the mass of the liquid carboxylated nitrile rubber, was added to the suspension, and the mixture was refluxed at 115℃ and atmospheric pressure for 1.5 h.

[0058] S3 Post-processing: After the reaction is completed, the reaction system is immediately cooled to room temperature in an ice-water bath. Anhydrous ethanol with a volume of 2.5 times the total volume of the reaction system is added to precipitate the solid product. The solid precipitate is completely collected by vacuum filtration. The filter cake is placed in a vacuum drying oven at 60℃ and a vacuum degree ≥-0.08MPa and dried to constant weight to obtain the interfacial hybrid nanocellulose reinforcing agent.

[0059] Preparation of aging-resistant rubber sealing ring materials: S1 Plasticizing: Place 90 parts by weight of EPDM rubber on an open mill, set the roll gap to 1.5 mm, and plasticize it 10 times in a thin pass at room temperature. Monitor the Mooney viscosity of the rubber compound in real time until the Mooney viscosity of the rubber compound is stably maintained in the range of 60±5 and the value of the test is stable for three consecutive times. The plasticizing of the base rubber is then completed.

[0060] S2 Mixing: The plasticized rubber compound is fed into a closed internal mixer. First, 10 parts by weight of interfacial hybrid nanocellulose reinforcing agent are added and mixed for 2.5 minutes. Then, 5.5 parts by weight of modified cage-type silsesquioxane antioxidant and 2 parts by weight of processing aid are added sequentially. High-purity nitrogen gas with a purity ≥99.5% is purged throughout the process for protection. A segmented speed-controlled mixing mode is adopted. In the first stage, the rotor speed is 40 rpm and the mixture is mixed at a constant temperature for 9 minutes. In the second stage, the rotor speed is increased to 60 rpm and the mixture is mixed at a constant temperature for 8.5 minutes. The total mixing time is 17.5 minutes. The discharge temperature is controlled not to exceed 100℃ throughout the process to obtain a uniformly dispersed compound. The vulcanization system is uniformly compounded from sulfur, accelerator DM, and accelerator TMTD in a mass ratio of 1:1:0.65. The particle size of the compounded vulcanization system powder is 250 mesh.

[0061] S3 Single-stage vulcanization molding: The prepared compound is transferred to a two-roll mill, and 3.5 parts by weight of the vulcanization system are added. The mixture is repeatedly rolled 6 times to ensure uniform dispersion of the additives throughout the compound. After sheeting, the compound is placed in a flat vulcanizing machine. It is then molded and vulcanized for 22.5 minutes at a vulcanization temperature of 160℃ and a vulcanization pressure of 12.5MPa to obtain the sealing ring preform. S4 Secondary vulcanization in nitrogen atmosphere: The vulcanized sealing ring preform is placed stably inside a nitrogen-filled oven, maintaining a nitrogen concentration ≥99.5% in the oven. The oven heating rate is controlled at 4℃ / min, and the mixture is heat-treated at a constant temperature of 170℃ for 3 hours. After heat treatment, the mixture is naturally cooled to room temperature and discharged to obtain the aging-resistant rubber sealing ring material.

[0062] Comparative Example 1: The preparation method provided in Example 1 was adopted, except that 3 parts by weight of modified cage-type silsesquioxane antioxidant were replaced with an equal mass of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate glycidyl ester, while the other raw material types, amounts and process parameters were completely consistent with those in Example 1.

[0063] Comparative Example 2: The preparation method provided in Example 1 was used, except that 5 parts by weight of the interfacial hybrid nanocellulose reinforcing agent were replaced with an equal mass of unmodified nanocellulose crystals, while the other raw material types, amounts and process parameters were completely consistent with those in Example 1.

[0064] Comparative Example 3: The preparation method provided in Example 1 is adopted, except that 3 parts by weight of modified cage-type silsesquioxane antioxidant are replaced with an equal mass of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate glycidyl ester, and 5 parts by weight of interfacial hybrid nanocellulose reinforcing agent are replaced with an equal mass of unmodified nanocellulose crystals. The other raw material types, amounts and process parameters are completely consistent with those in Example 1.

[0065] Comparative Example 4: The preparation method provided in Example 1 is adopted, except that the secondary vulcanization process in nitrogen atmosphere in step S4 is cancelled, and the material is directly cooled to room temperature after the first vulcanization is completed. The other raw material types, amounts and other process steps are completely consistent with those in Example 1.

[0066] test: Experiment 1: Hot Air Accelerated Aging Performance Test Test Method: Each specimen was stamped into a type 1 dumbbell shape and placed in a hot air aging chamber for continuous aging at 150℃ for 72 hours. Tensile strength and elongation at break were tested before and after aging. Five parallel samples were tested for each group of specimens, and the average value was taken. The performance retention rate was calculated using the formula: Performance retention rate = (Performance value after aging / Performance value before aging) × 100%. The tensile test rate was set to 500 mm / min, and the ambient temperature was 23℃. The test results are shown in the table below: Table 1 Results of hot air aging performance test

[0067] As shown in Table 1, the tensile strength retention rate of Examples 1-3 was all above 92%, and the elongation at break retention rate was all above 88%, indicating excellent aging resistance. Comparative Example 1 used a common hindered phenolic antioxidant without grafted cage-like silsesquioxane structures. The antioxidant molecules easily migrated and precipitated at high temperatures, failing to continuously block the free radical chain reaction of thermo-oxidative aging, resulting in a significant decrease in performance retention after aging. Comparative Example 2 used unmodified nanocellulose, which had little impact on aging resistance; only the weak interfacial bonding led to a slight decrease in matrix density, resulting in a minor performance reduction. Comparative Example 3 lacked both modifying agents, causing a simultaneous decrease in both anti-aging effect and matrix density, with the most significant aging performance degradation. Comparative Example 4 did not undergo secondary nitrogen vulcanization, resulting in an incomplete cross-linking network. Residual small-molecule additives easily migrated during aging, leading to a slight decrease in aging resistance.

[0068] Experiment 2: Mechanical property testing at room temperature: Test Method: Each specimen was stamped into a type I dumbbell shape. Tensile strength and elongation at break were tested using an electronic universal testing machine at a test rate of 500 mm / min and an ambient temperature of 23℃. Five parallel samples were tested in each group, and the average value was taken. The hardness of the specimens was tested using a Shore A hardness tester, with five different locations tested on each specimen, and the average value was taken. The test results are shown in the table below: Table 2 Results of mechanical properties at room temperature

[0069] As shown in Table 2, the tensile strength of Examples 1-3 is all higher than 18 MPa, indicating excellent mechanical properties. The replacement of the antioxidant in Comparative Example 1 has minimal impact on mechanical properties, suggesting that the modified antioxidant mainly improves aging resistance and has limited contribution to reinforcement. Comparative Example 2 uses unmodified nanocellulose. Due to the poor compatibility between the hydrophilic surface of cellulose and the rubber matrix, the interfacial bonding is weak, and the stress transfer efficiency is low, resulting in a significant decrease in tensile strength and hardness, and a corresponding decrease in elongation at break. Comparative Example 3, which replaces both additives simultaneously, suffers from the worst mechanical properties due to the combined effects of interfacial defects and insufficient reinforcement. Comparative Example 4, which does not undergo secondary vulcanization, has insufficient crosslinking density and poor crosslinking network uniformity, leading to a certain degree of decrease in mechanical properties.

[0070] Experiment 3: High-Temperature Compression Permanent Deformation Test Test Method: A type B cylindrical specimen with a diameter of 29 mm and a thickness of 12.5 mm was prepared. The specimen was placed in a compression fixture with a compression rate set to 25%, and then placed in a 120℃ oven for 24 hours. Immediately after removal, the compression load was released, and the specimen was allowed to recover freely at room temperature for 30 minutes. The thickness of the recovered specimen was measured, and the compression set was calculated using the formula: Compression Set = (Initial Specimen Thickness - Recovery Thickness) / (Initial Specimen Thickness - Restoration Fixture Thickness) × 100%. Three parallel specimens were tested in each group, and the average value was taken. The test results are shown in the table below: Table 3 Results of High Temperature Compression Permanent Deformation Test

[0071] As shown in Table 3, the compression set rates of Examples 1-3 were all below 20%, demonstrating excellent resistance to compression deformation and meeting the requirements for long-term sealing of the sealing rings. In Comparative Example 1, the ordinary antioxidant was prone to migration, and the matrix aging accelerated at high temperatures. The degradation of the cross-linked network led to a decrease in elastic recovery ability, resulting in a significantly higher compression set rate. In Comparative Example 2, voids existed at the interface between the unmodified nanocellulose and the matrix, making it prone to interfacial slippage and internal defects during compression, leading to a decrease in deformation recovery ability. Comparative Example 3 suffered from both insufficient anti-aging performance and poor interfacial bonding. The combined effect of cross-linked network destruction and interfacial slippage at high temperatures resulted in the highest compression set rate. Comparative Example 4, due to its imperfect cross-linked network and insufficient elastic recovery ability, also exhibited a higher compression set rate than the Examples.

[0072] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. An aging-resistant rubber sealing ring material, characterized in that, It is made from the following raw material components in parts by weight: 80-100 parts of base rubber, 3-8 parts of modified cage-type silsesquioxane antioxidant, 5-15 parts of interface hybrid nanocellulose reinforcing agent, 2-5 parts of vulcanization system, and 1-3 parts of processing aid. The modified cage-type silsesquioxane antioxidant is a monomolecular dispersible antioxidant prepared by grafting octaaminophenyl cage-type silsesquioxane with an epoxy-containing hindered phenolic compound.

2. The aging-resistant rubber sealing ring material according to claim 1, characterized in that, The base rubber is at least one of EPDM rubber, nitrile rubber, and fluororubber.

3. The aging-resistant rubber sealing ring material according to claim 1, characterized in that, The preparation method of the modified cage-type silsesquioxane antioxidant includes the following steps: An OAPS dispersion with a mass fraction of 5%-8% was prepared by uniformly dispersing octaaminophenyl cage-type silsesquioxane in anhydrous toluene. Under a high-purity nitrogen atmosphere and in an ice bath at 0-5°C, an anhydrous toluene solution of a hindered phenolic compound containing an epoxy group was slowly added dropwise to the dispersion. The molar ratio of octaaminophenyl cage-type silsesquioxane to the hindered phenolic compound containing an epoxy group was 1:1.5-2.

5. After the addition was completed, the temperature was uniformly raised to 75-85°C and refluxed for 6-10 hours. After the reaction is completed, 60%-70% of the anhydrous toluene solvent is removed by vacuum distillation of the reaction solution. Then, petroleum ether with a volume of 2-3 times that of the remaining reaction solution is added and the mixture is allowed to stand for 2-4 hours to precipitate. The solid precipitate is collected by vacuum filtration and the filter cake is washed three times with anhydrous toluene. The washed filter cake is then dried in a vacuum drying oven at 60-70℃ for 12-16 hours to obtain the modified cage-type silsesquioxane antioxidant.

4. The aging-resistant rubber sealing ring material according to claim 1, characterized in that, The hindered phenolic compound containing an epoxy group is glycidyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

5. The aging-resistant rubber sealing ring material according to claim 1, characterized in that, The preparation method of the interface hybrid nanocellulose reinforcing agent includes the following steps: S1 Hydrophobic Modification: A 2%-5% solid content aqueous dispersion of nanocellulose crystals was ultrasonically dispersed for 30-60 minutes at room temperature and 200-300W power. Silane coupling agent KH-570 was added at 8%-12% of the dry weight of the nanocellulose crystals. The pH of the system was precisely adjusted to 4-5 using glacial acetic acid. Modification was carried out for 2-3 hours under constant temperature water bath at 60℃ and uniform stirring. After modification, the solid product was separated by centrifugation at 8000-10000 r / min and repeatedly washed with deionized water until the filtrate was neutral, yielding hydrophobically modified nanocellulose. S2 Interface Grafting: The hydrophobic modified nanocellulose is uniformly dispersed in xylene solvent at a solid-liquid mass ratio of 1:20-30. Liquid carboxylated nitrile rubber with a dry weight mass ratio of 2-3:1 to the hydrophobic modified nanocellulose is added. The mixture is stirred at room temperature and 300-500 r / min for 30 min to form a homogeneous suspension. Dibutyltin dilaurate catalyst, accounting for 0.5%-1% of the mass of the liquid carboxylated nitrile rubber, is added to the suspension. The mixture is then refluxed at 110-120℃ under normal pressure for 1-2 h. S3 Post-processing: After the reaction is completed, the reaction system is immediately cooled to room temperature in an ice-water bath. Anhydrous ethanol with a volume of 2-3 times the total volume of the reaction system is added to precipitate the solid product. The solid precipitate is completely collected by vacuum filtration. The filter cake is placed in a vacuum drying oven at 60℃ and a vacuum degree ≥-0.08MPa and dried to constant weight to obtain the interfacial hybrid nanocellulose reinforcing agent.

6. The aging-resistant rubber sealing ring material according to claim 1, characterized in that, The vulcanization system is uniformly compounded from sulfur, accelerator DM, and accelerator TMTD in a mass ratio of 1:0.8-1.2:0.5-0.8, and the particle size of the compounded vulcanization system powder is 200-300 mesh.

7. The aging-resistant rubber sealing ring material according to claim 1, characterized in that, The processing aid is at least one of stearic acid, polyethylene wax, and paraffin wax.

8. A method for preparing an aging-resistant rubber sealing ring material according to any one of claims 1-7, characterized in that, Includes the following steps: S1 Plasticizing: Place the base rubber on a two-roll mill, set the roll gap to 1-2mm, and perform thin-pass plasticizing 8-12 times at room temperature. Monitor the Mooney viscosity of the rubber compound in real time until the Mooney viscosity of the rubber compound is stably maintained in the range of 60±5 and the value of the test is stable for three consecutive times without fluctuation. The plasticizing of the base rubber is then completed. S2 Mixing: The plasticized rubber compound is put into a closed internal mixer. First, the interfacial hybrid nanocellulose reinforcing agent is added and mixed for 2-3 minutes. Then, the modified cage-type silsesquioxane antioxidant and processing aid are added in sequence. High-purity nitrogen gas with a purity of ≥99.5% is introduced throughout the process for protection. The segmented speed-regulating mixing mode is adopted, and the total rotor speed range is controlled at 40-60 rpm. The total mixing time is 15-20 minutes. The discharge temperature is controlled not to exceed 100℃ throughout the process to obtain a uniformly dispersed compound. S3 One-Step Vulcanization Molding: The prepared compound is transferred to a two-roll mill, the proportioned vulcanization system is added, and the mixture is repeatedly rolled 5-8 times to ensure uniform dispersion of the additives throughout the compound. After sheeting and cutting, the mixture is placed in a flat vulcanizing machine. The preformed sealing ring is then molded and vulcanized for 20-25 minutes at a vulcanization temperature of 150-170℃ and a vulcanization pressure of 10-15MPa to obtain the sealing ring preform. S4 Nitrogen Atmosphere Secondary Vulcanization: The pre-formed sealing ring after vulcanization is placed stably inside a nitrogen-filled oven, maintaining a nitrogen concentration of ≥99.5% in the oven, and heat-treated at a constant temperature of 160-180℃ for 2-4 hours. After heat treatment, the material is discharged naturally to room temperature to obtain an aging-resistant rubber sealing ring material.

9. The method for preparing the aging-resistant rubber sealing ring material according to claim 8, characterized in that, Step S2 describes segmented mixing, which is divided into two speed-adjusting mixing stages: the first stage has a rotor speed of 40 rpm and constant temperature mixing for 8-10 minutes; the second stage increases the rotor speed to 60 rpm and constant temperature mixing for 7-10 minutes.

10. The method for preparing the aging-resistant rubber sealing ring material according to claim 8, characterized in that, During the secondary vulcanization process described in step S4, the oven heating rate is strictly controlled at 3-5℃ / min.